Pemetaan Rasionalitas Jaksa dalam Seleksi Perkara Korupsi Pendekatan Qualitative Comparative Analysis (QCA) - Methodius Kossay; Rengga Kusuma Putra (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2026)
Prosecutorial discretion in corruption case selection is often explained through linear causal models that emphasize single determinants such as evidentiary strength, institutional pressure, or case severity; however, such approaches are limited in capturing the configurational complexity of decision-making within prosecutorial institutions. This study aims to identify configurational pathways that lead to high prosecutorial priority in corruption case handling using fuzzy-set Qualitative Comparative Analysis (fsQCA). The study applies a configurational research design based on fsQCA, analyzing six causal conditions consisting of financial loss, actor complexity, public attention, evidence strength, institutional pressure, and asset recovery potential. Data are calibrated into fuzzy-set membership scores (0–1) using a direct calibration approach, followed by truth table construction, necessity analysis, sufficiency analysis, and Boolean minimization using intermediate solutions. The findings reveal three distinct causal pathways leading to high prosecutorial priority: institutionally reinforced legal rationality characterized by high financial loss, strong evidence, and high institutional pressure; visibility-driven prioritization combining actor complexity and public attention with moderate evidentiary strength; and technocratic fiscal rationality driven by high financial loss, high asset recovery potential, and low institutional pressure. No single condition is found to be necessary, confirming equifinality and causal asymmetry. Prosecutorial prioritization in corruption cases is therefore best understood as a configurational phenomenon shaped by multiple interacting rationalities rather than single causal factors, introducing the concept of configurational prosecutorial rationality within criminal justice decision-making.